Synthesis of self-aggregative zinc chlorophylls possessing polymerizable esters as a atable model compound for main light-harvesting antennas of green photosynthetic bacteria - Hitoshi Tamiaki; Kazuya Nishihara; Reiko Shibata (International Journal of Photoenergy)
Zinc bacteriochlorophyll-d derivatives possessing a polymerizable moiety at the 17-propionate were prepared as model compounds of natural occurring chlorophylls in the main peripheral antennas of green photosynthetic bacteria (chlorosomes). The synthetic compounds self-aggregated in nonpolar organic solvents as well as in the solid state to give large oligomers similar to chlorosomal J-aggregates. Such introduction of the polymerizable groups in the ester did not suppress the ability of self-aggregation.